أثر برنامج ترويحي رياضي مقترح على بعض المهارات الاجتماعية (الاستقلالية- التعاون) لدى المعاقين سمعيا - الشيخ, صافي (مجلة علوم وممارسات الأنشطة البدنية الرياضية والفنية جامعة الجزائر03, 2018)
The effect of the proposed sports recreation program on the social skills (autonomy, cooperation) of the hearing impaired The aim of the research is to find out the effect, of the proposed sports recreation program, on the autonomy and cooperation skills of the hearing impaired, To achieve this goal, we have assumed the following scientific hypothesis: The sports recreation program positively affects autonomy and cooperation skills, and this; in order to answer the following question: : Does the proposed sports recreation program improve the autonomy and cooperation skills of hearing impaired, for this purpose we used, a sample of 20 students from the hearing impaired school; between the ages of 09 and 12 years, divided into two groups, experimental and control groups, chosen deliberately from an original community of 75 students, where we used the experimental method, and the following statistical methods: The arithmetic mean, the standard deviation, the correlation coefficient, the test of validity, “T” test. After discussing the results, it was found that the proposed sport recreation program contributed to improving autonomy and cooperation skills in this sample. Finally, we came out with a set of recommendations and suggestions, most notably the use of recreational sports programs in hearing impaired schools due to its positive impact, the provision of hearing impaired schools with tools and means, as well as equipped halls and fields for the exercise of sports in hearing impaired schools--------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------L’influence d’un programme récréatif sportif proposé sur certaines habilités sociales (l'autonomie, coopération) sur les handicapés auditifs L’objectif de cette recherche est de reconnaitre L’influence d’un programme récréatif sportifs proposé sur l'autonomie et la coopération chez les handicapés auditifs, et Pour atteindre cet objectif, le chercheur a supposé l'hypothèse scientifique suivante: Le programme récréatif sportif influence positivement sur les habilités sociales. Et cela pour répondre à la question suivante : Le programme récréatif sportif influence-t-il dans l’amélioration de l'autonomie et la coopération chez les handicapés auditifs ? On se basant sur une étude de l’échantillon de 20 élèves de l’école des handicapés auditif leur âges varient 09 et 12 ans, divisés en deux groupes, expérimental et témoins, choisis d’une manière volontaire parmi une communauté originale de 75 élèves. Le chercheur a adopté une approche expérimentale, on se base sur un questionnaire et un programme .On utilisant les méthodes statistiques suivantes: La moyenne, l'écart type, le coefficient de corrélation, le test de student "T". Les résultats ont montré que le programme influe positivement sur certaines habilités sociales qui sont l'autonomie et la coopération Par conséquence le chercheur recommande l’adoption du programme proposé dans les écoles des handicapés auditifs --------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- أثر برنامج ترويحي رياضي مقترح على بعض المهارات الاجتماعية (الإستقلالية - التعاون) لدى المعاقين سمعيا (09 - 12) سنة يهدف البحث إلى معرفة أثر البرنامج الترويحي الرياضي المقترح على مهارات الإستقلالية و التعاون عند المعاقين سمعيا، و لتحقيق هذا الهدف إفترضنا الفرض العلمي التالي : يؤثر البرنامج الترويحي الرياضي إيجابيا على مهارات الإستقلالية و التعاون و ذلك للإجابة على السؤال التالي: هل يؤثر البرنامج الترويحي الرياضي المقترح في تحسين مهارات الإستقلالية و التعاون عند المعاقين سمعيا ، و لهذا الغرض إستعنا بعينة قوامها 20 تلميذا من مدرسة المعاقين سمعيا تتراوح أعمارهم بين 09 و 12 سنة مقسمين إلى مجموعتين تجريبية و ضابطة إختيرت بطريقة عمدية من مجتمع أصلي قوامه 75 تلميذا حيث إستخدمنا المنهج التجريبي ، وتمت الإستعانة بالوسائل الإحصائية التالية : المتوسط الحسابي الإنحراف المعياري ، معامل الإرتباط ، صدق الإختبار ، معامل دلالة الفروق * ت* . وبعد مناقشة النتائج تم التوصل إلى أن البرنامج الترويحي الرياضي المقترح ساهم في تحسين مهارات الإستقلالية و التعاون عند هذه العينة و في الأخير خرجنا بمجموعة من التوصيات و الإقتراحات أهمها إستخدام البرامج الترويحية الرياضية في مدارس المعاقين سمعيا لما لهلا من الأثرالإيجابي و توفير الأدوات و الوسائل و كذا القاعات المجهزة و الميادين اللازمة لممارسة الرياضة داخل مدارس المعاقين سمعيا .
Keywords: Recreation, autonomy , cooperation, hearing impaired; Récréative, l'autonomie, coopération, les handicapés auditifs; الترويح ، المعاقين سمعيا ، الإستقلالية ، التعاون